2020
DOI: 10.48550/arxiv.2011.08873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electromagnetic Signatures of Relativistic Explosions in AGN Disks

Rosalba Perna,
Davide Lazzati,
Matteo Cantiello

Abstract: The disks of Active Galactic Nuclei (AGNs), traditionally studied as the feeders of the supermassive black holes (SMBHs) at their centers, have recently triggered a lot of interest also as hosts to massive stars and hence their neutron star (NS) and black hole (BH) remnants. Migration traps and gas torques in these disks favor binary formation and enhance the rate of compact object mergers. In these environments both long gamma-ray bursts (GRBs) from the death of massive stars and short GRBs from NS-NS and NS-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…After the completion of this work, we learned that Perna et al (2020) have independently investigated the general properties of GRBs in an AGN disk. Different from our approach to focus on the characteristics of EM signals of BNS/NSBH mergers located at migration traps in AGN disks, they discussed the various possible outcomes of a GRB originating from different distances from the supermassive BH and different BH masses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…After the completion of this work, we learned that Perna et al (2020) have independently investigated the general properties of GRBs in an AGN disk. Different from our approach to focus on the characteristics of EM signals of BNS/NSBH mergers located at migration traps in AGN disks, they discussed the various possible outcomes of a GRB originating from different distances from the supermassive BH and different BH masses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…• Short GRB jets from neutron star mergers are more likely to be seen without being choked, but gamma-ray spectra may be modified. The mergers of BNS and NS-BH binaries are also expected in AGN disks, which can induce unique EM signals (e.g., Zhu et al 2020;Perna et al 2020). BNS and NS-BH mergers are expected to occur at the migration trap located in R < 10 3 (Bellovary et al 2016) or 10 −2 pc (corresponding to R ∼ 10 4 for M • = 10 7 M ⊙ ) suggested by dedicated numerical calculations (Tagawa et al 2020b).…”
Section: Summary and Implicationsmentioning
confidence: 98%
“…Recently, Zhu et al (2020) discussed the cases for binary neutron star and neutron star-black hole mergers and jet breakout emission from kilonova ejecta. Perna et al (2020) focused more generally on explosions in AGN disks and the ensuing breakout emission.…”
mentioning
confidence: 99%